2015
DOI: 10.1111/iwj.12557
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species (ROS) and wound healing: the functional role of ROS and emerging ROS‐modulating technologies for augmentation of the healing process

Abstract: Reactive oxygen species (ROS) play a pivotal role in the orchestration of the normal wound-healing response. They act as secondary messengers to many immunocytes and non-lymphoid cells, which are involved in the repair process, and appear to be important in coordinating the recruitment of lymphoid cells to the wound site and effective tissue repair. ROS also possess the ability to regulate the formation of blood vessels (angiogenesis) at the wound site and the optimal perfusion of blood into the wound-healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
687
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 941 publications
(700 citation statements)
references
References 60 publications
7
687
0
6
Order By: Relevance
“…The wound area, determined for various types of the 7-minute NTAP-treated sutures, didn’t show any statistically significant difference. As previously indicated in the literature, reactive oxygen species (ROS) generated with NTAP act as a signal molecule and accelerate the wound closure [5255]. In another study, Murrell et al reported that ROS significantly promotes the migration and proliferation of human fibroblasts [56].…”
Section: Discussionmentioning
confidence: 99%
“…The wound area, determined for various types of the 7-minute NTAP-treated sutures, didn’t show any statistically significant difference. As previously indicated in the literature, reactive oxygen species (ROS) generated with NTAP act as a signal molecule and accelerate the wound closure [5255]. In another study, Murrell et al reported that ROS significantly promotes the migration and proliferation of human fibroblasts [56].…”
Section: Discussionmentioning
confidence: 99%
“…Trx may be important for redox control at wound margins, since much ROS emergence was proven there [91, 92]. ROS as second messenger ameliorates wound healing processes [93]. Therefore, among others, it serves the migration of cells and closure of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is triggered and leads to the formation of granulation tissue, which is important to support the nutrients and oxygen supply in injured tissue [46]. In this tissue, fibroblasts become myofibroblasts which synthesize and deposit extracellular matrix (ECM) compounds, especially collagen.…”
Section: Introductionmentioning
confidence: 99%